Regional Resistance Value Optimization of Cerebral Blood Circulation - Bozkurt, Surhan; Ayten, Umut Engin (IEEE, 2021)
Cerebral blood flow supplies adequate oxygen and energy sources to the brain. Reduction in regional cerebral blood flow rates may lead to some neurological problems. In this study, a direct search optimization method was developed to adjust each resistance of lumped-parameter model of cerebral blood circulation for different physiological conditions. The developed method was tested by using a cardiovascular system model for both healthy and heart failure conditions. The mean blood flow rates of internal carotid and vertebral arteries supplying blood to the cerebral blood circulation were 271 mL/min and 106 mL/min over a cardiac cycle, respectively. In the case of heart failure, the mean blood flow rates of internal carotid arteries and vertebral arteries decreased to 190 mL/min and 74 mL/min over a cardiac cycle, respectively. The results show that regional resistance values of cerebral circulation model were optimized correctly for healthy and heart failure cases.
Keywords: cerebral circulation; parameter optimization; heart failure; Engineering